Ministry of Manpower and Immigration Decree No. 305 of the Year 2015 With Regard to The Conditions and Procedures of Granting Foreigners Work Permits = وزارة القوى العاملة والهجرة قرار رقم 305 لسنة 2015 بشأن شروط وإجراءات بالعمل للأجانب - Egypt; The middle east library for economic services, translator. (2025)
ministry of manpower and immigration Decree No. 305 of the year 2015 with Regard to the conditions and procedures of granting foreigners work permits وزارة القوى العاملة والهجرة قرار رقم 305 لسنة 2015 بشأن شروط وإجراءات الترخيص بالعمل للاجانب